2022
DOI: 10.1093/jxb/erac249
|View full text |Cite
|
Sign up to set email alerts
|

Two homeologous MATE transporter genes,NtMATE21andNtMATE22, are involved in the modulation of plant growth and flavonol transport inNicotiana tabacum

Abstract: Multidrug and toxic compound extrusion (MATE) family has been implicated in the transport of a diverse range of molecules, including specialized metabolites. In Nicotiana tabacum, only a limited number of MATE transporters have been functionally characterized, and no MATE transporter has been studied in the context of flavonoid transport in this plant species so far. Here in the present study, we characterize two homeologous MATE genes, NtMATE21 and NtMATE22, and demonstrate their role in flavonol transport an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…It was reported that MATEs could affect the expression levels of the genes involved in the anthocyanin synthesis pathway. For example, the expression levels of NtCHI1 , NtCHI2 , NtF3H1 , NtF3H2 , NtFLS1 , and NtFLS2 were downregulated in NtMATE‐amiR knockdown lines, but the expression level of NtCHS3 and NtCHS4 genes were not found to be significantly downregulated (Gani et al, 2022). In addition, the UDP‐glycosyltransferase gene was up‐regulated when OsMATE1 was overexpressed in Arabidopsis (Tiwari et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that MATEs could affect the expression levels of the genes involved in the anthocyanin synthesis pathway. For example, the expression levels of NtCHI1 , NtCHI2 , NtF3H1 , NtF3H2 , NtFLS1 , and NtFLS2 were downregulated in NtMATE‐amiR knockdown lines, but the expression level of NtCHS3 and NtCHS4 genes were not found to be significantly downregulated (Gani et al, 2022). In addition, the UDP‐glycosyltransferase gene was up‐regulated when OsMATE1 was overexpressed in Arabidopsis (Tiwari et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…NtMATE21 and NtMATE22 were identified in Nicotiana tabacum and found to play important roles in plant growth and flavonol transport. Genetic manipulation of the two transporter genes resulted in altered growth phenotypes and modulated the levels of flavonol in Nicotiana tabacum (Gani et al, 2022). Petunia hybrida is one of the most popular ornamental plants in the world and is one of the ideal plants to study plant flower color.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, flavonoids are biosynthesized in the cytoplasm and then transferred to the vacuole for storage before petal coloring. Therefore, this usually involves some flavonoid transporters that may also affect flower color, such as multidrug and toxic extrusion (MATE) and glutathione S-transferase (GST) (Cao et al, 2021;Chen et al, 2015;Gani et al, 2022;Gao et al, 2016a;Gomez et al, 2009;Han et al, 2022).…”
Section: Molecular Mechanism Affecting the Color Difference Of Double...mentioning
confidence: 99%
“…Experiments have shown that uptake of exogenous flavonoids is an active transport, and mediated by ABC transporters. Intracellular and inter-cellular transport of endogenous flavonoids have also been reported, which has been shown to be mediated by ABCC, P-ATPase and MATE families of transporters (20, 22, 23). Glutathione S-transferase like proteins called ligandin has been recently identified to protect flavonoids during vacuolar transport (24).…”
Section: Introductionmentioning
confidence: 99%